2021
DOI: 10.3746/jkfn.2021.50.5.464
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics and Antioxidant Activity of Rye Cookies Supplemented with Sea Buckthorn Leaf Powder

Abstract: This study investigated the quality characteristics and antioxidant activity of rye cookies prepared using sea buckthorn leaf powder (SBLP), which is known to contain various functional ingredients. Rye cookies were prepared by replacing 0%, 3%, 5%, 7%, and 9% flour with SBLP. The pH of cookie dough was significantly decreased with increasing amount of added SBLP. The loss and leavening rate of cookie also showed a similar decreasing tendency, whereas the moisture content and sweetness of cookie were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…https://doi.org/10.11002/fsp.2024.31.2.245 in the present study was 0.17 g/mL across all samples without any significant variation, which agreed with the results of a previous study on rice cookies supplemented with Tenebrio molitor larvae, Protaetia cataphracta larvae, and Gryllus bimaculatus powder (Jang et al, 2022). Park and Joo (2021) also showed that sea buckthorn leaf powder content had no effect on sample density, which was attributed to the fact that this content was low and indicated that it did not significantly impact cookie quality. The lack of density change observed herein was therefore ascribed to the relatively low MP content.…”
Section: Proximate Compositions Of Mp and Mymentioning
confidence: 96%
See 2 more Smart Citations
“…https://doi.org/10.11002/fsp.2024.31.2.245 in the present study was 0.17 g/mL across all samples without any significant variation, which agreed with the results of a previous study on rice cookies supplemented with Tenebrio molitor larvae, Protaetia cataphracta larvae, and Gryllus bimaculatus powder (Jang et al, 2022). Park and Joo (2021) also showed that sea buckthorn leaf powder content had no effect on sample density, which was attributed to the fact that this content was low and indicated that it did not significantly impact cookie quality. The lack of density change observed herein was therefore ascribed to the relatively low MP content.…”
Section: Proximate Compositions Of Mp and Mymentioning
confidence: 96%
“…In a previous study on rice cakes supplemented with MP (Nam and Sim, 2021), pH increased with the increasing MP content, in line with the results presented herein. Park and Joo (2021) reported that the pH of sea buckthorn leaf powder was lower than that of flour and thus rationalized the decrease in dough pH with the increasing MP content. Thus, the increase in the dough pH with the increasing MP content observed herein was ascribed to the lower pH of flour (5.99) compared with that of MP (6.93).…”
Section: Ph and Sugar Contents Mp And My Doughmentioning
confidence: 97%
See 1 more Smart Citation